Evaluating the efficacy of the anticancer drug cetuximab by atomic force microscopy. Issue 39 (13th June 2018) - Zhang, Qingrong; Shi, Yan; Xu, Haijiao; Zhou, Lulu; Gao, Jing; Jiang, Junguang; Cai, Mingjun; Shan, Yuping
Abstract : Atomic force microscopy can be implemented as a platform for further investigations that target the cellular stiffness and affinity of ligand–receptor as a therapeutic choice. Abstract : Cetuximab is a monoclonal antibody that binds to the epidermal growth factor receptor, which is important in the growth of many cancers. However, the biophysical characteristics of cetuximab as an anti-cancer drug remain elusive. In this study, we adopted atomic force microscopy to measure the mechanical properties of cancer cells following cetuximab treatment and the biomechanical properties of cetuximab and epidermal growth factor receptor interactions. Atomic force microscopy can be implemented as a platform for further investigations that target the cellular stiffness and affinity of ligand–receptor as a therapeutic choice.